Burnout prevalence in medical students attending a team-based learning school - Kushida, Simone Sayuri; Troster, Eduardo Juan (Frontiers in Education, 2023)
Introduction Worldwide burnout prevalence among medical students is high. It has a negative impact on students’ personal and professional lives as well as on their psychosocial wellbeing and academic performance. It can result in physicians with emotional distancing and indifference to work, and it compromises the quality of healthcare offered to society. This study evaluates burnout in medical students selected by mini-multiple interviews (MMIs) who were being taught by the team-based learning (TBL) method. MMIs are often used to select students with soft skills for medicine, and TBL is related to greater academic achievement, which would allow students to have greater resilience to stress. Information on burnout occurrence is lacking for this type of student. Methods Students (N = 143) attending the first three semesters at a private medical school were evaluated. The Copenhagen Burnout Inventory—Student Version (CBI-SV) questionnaire was applied on three occasions (applications = Apps one, two, and three) in each semester. Scores ≥ 50 were considered to indicate burnout. Data were analyzed by statistics programs. Results Personal-related and study-related burnout frequencies for 1st semester students were, respectively, 24.4 and 22% in App one and rose to 51 and 48.5% at the semester’s end. Second- and third-semester students’ frequencies reached 80.4 and 78.8%, respectively. Around 40% of 1st semester students having burnout at App one maintained the burnout score. Peer- and teacher-related burnout frequencies are low (4.9 and 2.4%) at the 1st semester App one and rose to the highest (24–30%) by the end of the 2nd semester. Woman students had significantly higher burnout frequencies in the personal- (p < 0.001) and study-related burnout subscales (p = 0.003). Students living with friends had lower study-related burnout scores than those living with family or alone (p = 0.024). There were no significant correlations between the burnout scores and tuition funding (partial or total) or having or not having religious faith. Discussion The prevalence of personal- and study-related burnout among medical students of the Faculdade Israelita de Ciências da Saúde Albert Einstein (FICSAE), perceived via mini-multiple interviews (MMI)—selected and team-based learning (TBL)—taught, was similar to those internationally reported. The college semester and the gender of woman were associated with worse burnout levels. Additional studies are needed to support more effective actions to reduce the impact of stress on students.